Self-Esteem and Loneliness: A Meta-Analysis Study - Pramodana Medha Wisesa; Eny Purwandari (Universitas Muhammadiyah Surakarta, 2024)
Loneliness can trigger many problems such as social media addiction, online bullying and phubbing. Even if often ignored can trigger self-harm behavior and give rise to suicidal ideation. Many factors can influence loneliness, including one of them (which is indirectly) self-esteem. Several studies show positive and negative correlation results, some even show that self-esteem does not affect loneliness. This meta-analysis aims to see the precision value between self-esteem and loneliness, using previous research data with a larger sample size to reduce bias in the analysis, through the process of correcting sampling errors and measurement errors, so that the precision value of the correlation coefficient is obtained. The research data comes from the publication of articles over the past 10 years (2012-2022), with a sample of 21 articles that meet the criteria, originating from Google Scholar, PubMed, Pro-Quest, Springerlink, Garuda through keyword searches related to loneliness and self-esteem. The overall results of this study show a correlation coefficient of -0.61 which means that someone with high self-esteem rarely feels lonely. The sampling error and measurement error of this study were small (3.08%). The sample was divided into 3 main parts, namely students, college students, and elderly. The strongest correlation was found in the student sample (-0.76). Further research should pay attention to how the distribution of countries and variable factors other than self-esteem.